The Role of Arbitral Tribunals in Investigating Corruption Allegations in International Commercial Contracts: An Analytical and Comparative Study - AL-Tarawneh, Mosleh Ahmad; Alhrerat , Khalid Abdulrahman (Dirasat: Shari'a and Law Sciences, 2021)
This research examines the powers of arbitral Tribunals in investigating the allegations of corruption in international commercial contracts which are the subject matter of international commercial arbitration proceedings, whether corruption is at the heart of contracts themselves or in the manner of obtaining them. The research discusses also the role of arbitral tribunals in addressing corruption issues and the controversy concerning that power and the standards of burden of corruption proof, including the conflict between the duty to report suspicions of corruption and the duty to adhere to confidentiality and the impermissibility of arbitrators addressing a matter not raised by the litigants. Despite international and national legislation consensus on condemnation and fighting of corruption, there are still legal differences regarding some practices that are criminalized by some legislation and permitted by others, such as facilitation payments and trading in influence. The research has followed up these legal differences and their impact on various trends of international arbitration. This research has also included presentation of standards adopted by arbitration tribunals to prove corruption, as well as the rules that are used to resolve the conflict between the applicable laws, and then examine the effects of corruption on arbitral awards. At the end, the researchers have concluded a set of findings and suggestions related to the research problems, including the inclusion of private sector into the concept of corruption, lifting the veil of arbitration confidentiality in corruption suspicious transactions and encouraging the use of adverse inference standard of proof in corruption cases.